2021
DOI: 10.3390/nu13072358
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Risk of Contamination of Food for Infants and Toddlers

Abstract: Infants and toddlers are highly sensitive to contaminants in food. Chronic exposure can lead to developmental delays, disorders of the nervous, urinary and immune systems, and to cardiovascular disease. A literature review was conducted mainly in PubMed, Google Scholar and Scopus databases, and took into consideration papers published from October 2020 to March 2021. We focused on contaminant content, intake estimates, and exposure to contaminants most commonly found in foods consumed by infants and children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 110 publications
0
8
0
1
Order By: Relevance
“…Mean Pb concentrations (µg/kg) were reported by Wang et al [ 32 ] in eight cereal-based foods; forty-five samples of beans, nuts, and derivatives; seven dairy products; twelve plant-based foods; six fruits and derivatives; and three samples of water and beverages. Mielech et al [ 53 ] conducted a survey on the risk of contamination of baby and infant foods, including Pb. A study showed that 96% of infant formulas exceeded the daily allowable Pb concentration (0.4 mg/kg), while another study reported that 37% of infant samples had Pb contamination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean Pb concentrations (µg/kg) were reported by Wang et al [ 32 ] in eight cereal-based foods; forty-five samples of beans, nuts, and derivatives; seven dairy products; twelve plant-based foods; six fruits and derivatives; and three samples of water and beverages. Mielech et al [ 53 ] conducted a survey on the risk of contamination of baby and infant foods, including Pb. A study showed that 96% of infant formulas exceeded the daily allowable Pb concentration (0.4 mg/kg), while another study reported that 37% of infant samples had Pb contamination.…”
Section: Resultsmentioning
confidence: 99%
“…A study showed that 96% of infant formulas exceeded the daily allowable Pb concentration (0.4 mg/kg), while another study reported that 37% of infant samples had Pb contamination. In addition, higher Pb levels were reported in rice-based products [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Un 48% de los expendedores utilizan la Zarzaparrilla y un 52% utilizan la Cebada reemplazando una a otra. El desconocimiento de las Buenas Prácticas de Manipulación de los alimentos aumenta el riesgo de contaminación del emoliente y la presencia de microorganismos, enfermedades de transmisión alimentaria siendo de gran importancia la capacitación constante a los expendedores de emoliente para poder evitar cualquier tipo de contaminación y propagación de enfermedades 6 . Respecto al grado de instrucción que tienen los expendedores de emoliente de la ciudad de Puno, se observa que el 76% tiene un grado de instrucción entre primaria completa y superior (primaria completa, secundaria completa, superior técnico, superior universitario) el 8% tiene grado de instrucción incompleto (primaria incompleta, secundaria incompleta) y el 16% no tiene estudios 7 .…”
Section: Resultados Figura 1 Ingredientes Para La Preparación Del Emo...unclassified
“…Despite the unquestionable nutritional bene ts of this practice, complementary foods, including infant formulas, may expose infants to chemical contaminants, including mycotoxins. Infants are considered more susceptible than adults to chemical contaminants and the safety of foods consumed by this population is a priority public health issue (Sherif et al 2009;Mielech et al, 2021).…”
Section: Introductionmentioning
confidence: 99%